Update on the fluorometric measurement of enzymatic activities for Lysosomal Storage Disorder detection: The example of MPS VI - Franco, Paula Gabriela (2017)
Lysosomal Storage Disorders (LSD) are rare diseases that as a whole havea combined incidence ranging from 1:1500 to 1:7000 live births. One of suchdiseases is Mucopolysaccharidosis VI (MPS VI), or Maroteaux Lamy Syndrome.MPS VI patients undergo devastating and irreversible skeletal alterations andmultisystemic failure as from early childhood due to reduced Arylsulfatse B(ARSB) enzyme activity.Reaching a final diagnosis is not always a short cut path, but rather a yearslongbattle against uncertainty and unnecessary medical interventions. Ouraim is to contribute from the bench table with different approaches that couldserve as alternatives to pre-existing assays for screening and diagnosing MPSVI and other LSD.The present work is based on our research article authored by Franco etal.1 where we studied the effect of blood-derived hemoglobin, and other bloodcomponents, on the fluorescence of 4-Methylumbelliferone when measuringARSB enzyme activity from dried blood spot (DBS) samples.Our experience indicates that to date there are plenty of differentapproaches for measuring ARSB enzyme activity, although the sample typerequired or the assay in itself often make them more adaptable for either highthroughput screening or small scale diagnostics.As a whole, the fluorometric determinations seem to be the mostaccessible to low budget laboratories with equally valuable performancesas a sophisticated mass spectrometry analysis for this disease. Furthermore,the DBS serves as an attractive sample type for screening the disease in largepopulations.